Effect of different phosphate sources on uranium biomineralization by the Microbacterium sp. Be9 strain: A multidisciplinary approach study - Martínez-Rodríguez, Pablo; Sánchez-Castro, Iván; Ojeda, Jesús J.; Abad, María M.; Descostes, Michael; Merroun, Mohamed Larbi (Frontiers in Microbiology, 2023)
Industrial activities related with the uranium industry are known to generate hazardous waste which must be managed adequately. Amongst the remediation activities available, eco-friendly strategies based on microbial activity have been investigated in depth in the last decades and biomineralization-based methods, mediated by microbial enzymes (e.g. phosphatase), have been proposed as a promising approach. However, the presence of different forms of phosphates in these environments plays a complicated role which must be thoroughly unravelled to optimize results when applying this remediation process. In this study, we have looked at the effect of different phosphate sources on the uranium (U) biomineralization process mediated by Microbacterium sp. Be9, a bacterial strain previously isolated from U mill tailings. We applied a multidisciplinary approach (cell surface characterization, phosphatase activity, inorganic phosphate release, cell viability, microscopy, etc.). It was clear that the U removal ability and related U interaction mechanisms by the strain depend on the type of phosphate substrate. In the absence of exogenous phosphate substrate, the cells interact with U through U phosphate biomineralization with a 98% removal of U within the first 48h. However, the U solubilization process was the main U interaction mechanism of the cells in the presence of inorganic phosphate, demonstrating the phosphate solubilizing potential of the strain. These findings show the biotechnological use of this strain in the bioremediation of U as a function of phosphate substrate: U biomineralization (in a phosphate free system) and indirectly through the solubilization of orthophosphate from phosphate (P) containing waste products needed for U precipitation.